Pathology of dogs in Campo Grande, MS, Brazil naturally co-infected with Leishmania infantum and Ehrlichia canis - Andrade, Gisele Braziliano; Gomes Barreto, Wanessa Teixeira; Santos, Luciana Ladislau dos; Rios Ribeiro, Laura Raquel; Macedo, Gabriel Carvalho de; Marques de Sousa, Keyla Carstens [UNESP]; Andre, Marcos Rogerio [UNESP]; Machado, Rosangela Zacarias [UNESP]; Herrera, Heitor Miraglia (Brazilian Coll Veterinary Parasitology, 2014)
Different parasites that commonly occur concomitantly can influence one another, sometimes with unpredictable effects. We evaluated pathological aspects of dogs naturally co-infected with Leishmania infantum and Ehrlichia canis. The health status of the dogs was investigated based on histopathological, hematological and biochemical analyses of 21 animals infected solely with L. infantum and 22 dogs co-infected with L. infantum and E. canis. The skin of both groups showed chronic, predominantly lymphohistioplasmacytic inflammatory reaction. The plasmacytosis in the lymphoid tissues was likely related with the hypergammaglobulinemia detected in all the dogs. The disorganization of extracellular matrix found in the reticular dermis of the inguinal region and ear, characterized by the substitution of thick collagen fibers for thin fibers, was attributed to the degree of inflammatory reaction, irrespective of the presence of parasites. In addition, the histopathological analysis revealed that twice as many dogs in the co-infected group presented Leishmania amastigotes in the ear skin than those infected solely with Leishmania, increasing the possibility of becoming infected through sand fly vectors. Our findings highlight the fact that the health of dogs infected concomitantly with L. infantum and E. canis is severely compromised due to their high levels of total plasma protein, globulins, alkaline phosphatase and creatine kinase, and severe anemia.

A infecção simultânea por parasitas de diferentes espécies pode resultar em alterações imprevisíveis. O presente estudo avaliou a patologia de cães naturalmente coinfectados por Leishmania infantum e Ehrlichia canis. A saúde dos cães foi investigada pelas análises histopatológicas, hematológicas e bioquímicas de 21 cães infectados somente por L. infantum e 22 cães coinfectados por L. infantum e E. canis. Observou-se uma reação inflamatória crônica, predominantemente linfohistioplasmocítica, na pele dos dois grupos. A plasmocitose, encontrada nos tecidos linfóides, provavelmente estava relacionada com a hipergamaglobulinemia observada em todos os cães amostrados. A desorganização da matriz extracelular da derme da região inguinal e da orelha, demonstrada pela substituição das fibras de colágeno espessas por fibras finas, foi relacionada com o grau de reação inflamatória, independente da presença de parasitas. Ainda, observamos duas vezes mais animais do grupo coinfectado apresentando formas amastigotas na pele de orelha pela histopatologia comparado ao número de cães infectados apenas por Leishmania, tornando-os desta forma mais infectivos aos vetores. Nossos resultados ressaltam que a saúde de cães coinfectados estava severamente comprometida devido aos altos níveis de proteína plasmática total, globulinas, fosfatase alcalina, creatina quinase e anemia acentuada.
Patologia de cães naturalmente coinfectados por Leishmania infantum e Ehrlichia canisem Campo Grande, MS, Brasil
Keywords: Canine leishmaniasis; canine ehrlichiosis; histopathology; concomitant infections; Leishmaniose canina; Erliquiose canina; Histopatologia; Infecções concomitantes